(3GdJMdjd Gdafj ddCShGb GdeGdjIs - (3YHO GdeLjO(B, (3Gdegjdejs; (3MGRe(B, (3GdHHdGhjs ((3GdbGgQI(B:s (3GdHdGZ ddWHGYI hGdfTQ hGdJhRjY(B,s, 2006)
(3GdGSJKeGQ,GdJYGed aj GdHhQUI eVGQHI Ce ebGeQI,JYQja GdJMdjd Gdafj,CfhGY GdQShe GdHjGfjI,GJLGgGJ GdCSYGQ GdKdGKI,GdOYe h GdebGheI,COhGJ JMdjdjI eJfhYI,GdCfeGW GdSYQjI,GdeJhSWGJ GdeJMQcI,GdePHPHGJ,fXQjGJ hJMdjdGJ eJbOeI,GdTehY GdjGHGfjI,EOGQI GdCehGd hhba GdNSGQI,bGehS eUWdMGJ GdJMdjd Gdafj GdEfLdjRjIs
(3HHdjhZQGajG(B:(3U(B.315-318 (3GdQShe GdHjGfjI(B:(3U(B.320-321s
Keywords: (3GdCSges; (3GdHhQUIs